Erythematous papular rash after international travel - Amaral de Moura, Luana; Emerich Nogueira, Paulo Sergio; Martins Diniz, Lucia; Neves Souza, Emilly (Revista de Patologia Tropical / Journal of Tropical Pathology, 2022)
Bed bugs are hematophagous ectoparasites usually found in bedsteads mattresses, and sheets. The bed bug infestations have been increasing dramatically, but only a few cases have been reported in Brazil. We presented a case of a 49-year-old woman with diffuse, extremely itchy skin lesions, after she returned from an international travel. KEY WORDS: Cimicidae; bedbugs; prurigo